2017
DOI: 10.1177/1687814017704356
|View full text |Cite
|
Sign up to set email alerts
|

Gear tooth surface damage diagnosis based on analyzing the vibration signal of an individual gear tooth

Abstract: Gear failure is the main cause of machine malfunction. Therefore, it has become increasingly important to detect gear failure to ensure the normal operation of a machine. Here, we propose a gear damage detection and localization approach by studying the vibration signal of an individual gear tooth and support vector machines. Generally, it is difficult to detect a small gear failure in the total vibration signal. The waveform of an individual gear tooth was studied to investigate the vibration features of a ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In the present work, it is proposed to fuse the HI value extracted from the same type of sensor but from different positions on the gearbox. In the literature, researchers 38,39 used the principal component analysis (PCA) approach for the parameter fusion. However, the fusion made based on the PCA algorithm loses interpretability.…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, it is proposed to fuse the HI value extracted from the same type of sensor but from different positions on the gearbox. In the literature, researchers 38,39 used the principal component analysis (PCA) approach for the parameter fusion. However, the fusion made based on the PCA algorithm loses interpretability.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the TSA time domain waveform is cleaner/purer compared to the original signal. 107 Some signal processing techniques are developed 108110 in which tachometer signal information can be extracted from the vibration signal itself and hence TSA can also be performed without the need of a separate tachometer sensor.…”
Section: Data-driven Approachesmentioning
confidence: 99%
“…Another way for HI space selection is to fuse all the indicators in such a way that it reduces the dimensionality of the extracted indicator space and at the same time retains the sensitivity or variability of all the indicators. Algorithms such as PCA, 107,[189][190][191][192][193][194][195] ICA, 191 and Mahalanobis distance (MD) 196 are widely used for indicator fusion/compression.…”
Section: Processing/selection Of the Hismentioning
confidence: 99%
“…These statistical values are used for the detection of faults in gears by wear, using vibration signals with outstanding results. For example, Fan et al [35] reported a gear damage diagnosis and classification using support vector machines based on statistical parameters, in the time domain.…”
Section: Design and Development Of The Upgrade Kitmentioning
confidence: 99%